2021
DOI: 10.1111/1556-4029.14783
|View full text |Cite
|
Sign up to set email alerts
|

Back to Amido Black: Uncovering touch DNA in blood‐contaminated fingermarks

Abstract: The investigation of serious crime scenes, such as murder by stabbing, requires a meticulous reconstruction of the events that have led to the crime and can be based, among others, on the analysis of blood stains that could help to connect the suspect to the victim and to the crime scene. In particular, blood-contaminated fingermarks (FMs) that are commonly found on surfaces such as plaster walls in crime scenes [1] may provide crucial evidence to the Crime Scene Investigation (CSI) units for the identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…直至 2021 年, Harush-Brosh 等 [35] 发现, 虽然 AB 会导 Mattson 等 [36] 比较了 5 种检测试剂的性能, 发现考马 斯亮蓝对于多孔和无孔表面稀释率为 1/25 的稀释血 指印检测效果最佳, 且其对于瓷砖表面稀释率高达 1/125 倍的血指印同样具有增强效果. 然而, Tsai 等 [37] 的研究表明, 考马斯亮蓝对遗传物质存在一定的生…”
Section: 其他unclassified
“…直至 2021 年, Harush-Brosh 等 [35] 发现, 虽然 AB 会导 Mattson 等 [36] 比较了 5 种检测试剂的性能, 发现考马 斯亮蓝对于多孔和无孔表面稀释率为 1/25 的稀释血 指印检测效果最佳, 且其对于瓷砖表面稀释率高达 1/125 倍的血指印同样具有增强效果. 然而, Tsai 等 [37] 的研究表明, 考马斯亮蓝对遗传物质存在一定的生…”
Section: 其他unclassified
“…Various studies have explored the compatibility of common fingerprint processing methods with DNA typing results [ [178] , [179] , [180] , [181] , [182] , [183] , [184] , [185] , [186] , [187] , [188] ]. For example, DNA recovery was explored after various steps in three different latent fingerprint processing methods – and fewer treatments were judged preferable with a 1,2-indanedione-zinc (IND/Zn) method appearing least harmful to downstream DNA analysis [ 187 ].…”
Section: Advancements In Current Practicesmentioning
confidence: 99%
“…Impact on DNA – Harush-Brosh et al emphasized a peculiar phenomenon linked to the application of AB (WEAA formulation) on blood fingermarks left on painted plaster wall surfaces [ 443 ]. In their experiments, the authors showed that AB partially inhibited the recovery of DNA from blood marks, whereas no such inhibiting effect was observed on non-bloody fingermarks.…”
Section: Fingermark Visualisationmentioning
confidence: 99%